Penguatan Nilai-Nilai Keagamaan melalui Laboratorium Sosial di Tanah Datar (Strengthening Religious Values through Social Laboratory in Tanah Datar) - Irwandi Irwandi; Zulamri Zulamri (Jurnal Dakwah Risalah, 2020)
The social laboratory functions for the expansion and strengthening of social science knowledge in universities. This study aims to determine the role and function of social laboratories in strengthening religious values in Tanah Datar District. This research uses a qualitative method with a descriptive approach. This research found that social laboratory activities started in preparation, programming, implementation, and evaluation. Laboratory activities include religious social literacy, religious social activities, and religious social documentation. The implication of the activity can be seen from the role of the social laboratory in helping the community to develop religious activities. A social laboratory is a place for applying science, especially in the field of community empowerment. The presence of social laboratories is the contribution of universities in the field of developing religious activities.